Additive manufacturing of functionally graded materials: A review - Zhang, Chi; Chen, Fei; Huang, Zhifeng; Jia, Mingyong; Chen, Guiyi; Ye, Yongqiang; Lin, Yaojun; Liu, Wei; Chen, Bingqing; Shen, Qiang; Zhang, Lianmeng; Lavernia, Enrique J. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2019)
Functionally graded materials (FGMs) represent a class of novel materials in which compositions/constituents and/or microstructures gradually change along single or multiple spatial directions, resulting in a gradual change in properties and functions which can be tailored for enhanced performance. FGMs can be fabricated using a variety of well-established processing methods; however, it is also known that there are inherent drawbacks to existing synthesis methods. As an emerging technology that provides a high degree of control over spatial resolution, additive manufacturing (AM) provides an intriguing pathway to circumvent the drawbacks of currently available methods. AM involves the selective deposition of individual layers of single or multiple materials, and as such it offers the potential of local control of composition and microstructure in multiple dimensions; such process conditions, in principle, can be tailored to construct complex FGMs with multi-dimensional and directional gradient structures. In this review paper, our current understanding of important issues, such as modeling, processing, microstructures and mechanical properties, as related to FGMs produced via AM, are described and discussed in an effort to assess the state of the art in this field as well as to provide insight into future research directions.